Defeating anorexia athletica : one woman's journey through exercise addiction and beyond - Maclean, Marion E., 1964- (Burleigh mdc, Qld. : Zeus Publications, 2010)
A true story charting the author's life-threatening battle with anorexia athletica - obsessive-compulsive exercise addiction. Her story takes the reader on a compelling and often painful journey that touches on the complexities of our fixation with physical perfection, eating disorders and obsessive-compulsive disorders.
At head of title: True story.
Includes bibliographical references.
Keywords: Maclean, Marion E., -- 1964-; Exercise addiction; Obsessive-compulsive disorder; Self-actualization (Psychology)